PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR TEMATIK TERPADU KELAS III SDN 19 PASAR AMBACANG - Puspita, Vivi; Al Husna, Hanifah (LP2M Universitas Adzkia, 2023)
Research was motivated by the low achievement of student learning outcomes in mathematics lessons. This happens because students do not play an active role in learning and teacher assessments still use manual methods. This problem can be seen from the students' scores which are still below the Minimum Learning Completeness (KBM). This research aims to determine the effect of quizizz on student learning outcomes in class V mathematics subjects at SDN 9 Kunpar, Sijunjung Regency. This research is an experimental research with a Quasi Experimental design and a Randomized Posttest Only Control research design. The population in this study was class V students at SDN 9 Kunpar, Sijunjung Regency, 2021/2022 academic year, totaling 40 students. Sampling used saturated samples, and the two classes that were the research subjects were class VA as the experimental class, class VB as the control class. Based on the results of hypothesis testing using the t test method, the data obtained is a value of tcount = 5.475 with a difficulty level of 5% with the test criteria if tcount > ttable then H1 is accepted and H0 is rejected. Where the number of test takers in the experimental class was 21 students with an average of 88, while in the control class the number of test takers was 19 people with an average of 77. The standard deviation of the experimental class (S=5.6) was lower than the control class (S= 7.2). The results of the t test are tcount= 5.475 and ttable=1.684. From the research results, it is proven that the use of Quizizz web has an influence on students' mathematics learning outcomes on scales and plans in class V of SDN 9 Kunpar, Sijunjung Regency, 2021/2022 academic year